Excellent Results from Controlled Donation after Circulatory Death Donors Using Abdominal Normothermic Regional Perfusion. (August 2017) - Minambres, Eduardo; Lavid, Nuria; Arlaban, Maite; Valero, Rosalia; Gómez-Ruiz, Marcos; Gonzalez-de la Guerra, Jose Manuel; Ponton, Alejandro; Ballesteros, Maria Angeles; Suberviola, Borja
Abstract : Background: Donation after circulatory death (DCD) has experienced a significant expansion over the last decade. However, warm ischemia results in a greater risk for transplantation. Indeed, controlled DCD (cDCD) was associated with inferior outcomes compared to donation after brain death. The use of abdominal normothermic regional perfusion (nRP) to restore blood flow prior to organ recovery in cDCD has been proposed as a better alternative than rapid recovery (RR) to reverse the effect of ischemia and improve recipients´ outcome. Methods: A single-center retrospective review of all actual cDCD procedures, from the start of the programme in September 2014 to April 2017, using abdominal nRP as in situ conditioning method is reported. Comparison between cDCD and DBD donors and recipients are performed with the Student's t-test or the Mann–Whitney U-test for continuous variables according to the sample distribution and the Kolmogorov–Smirnov/Shapiro–Wilk normality testing. For comparisons of categorical variables the χ2 test is used with the Fisher correction where applicable. Patient and graft survival is studied by the Kaplan–Meier method and compared with the log-rank test. Results: Thirty-five cDCD donors underwent abdominal nRP (September 2014-April 2017). Donors in our series were much older (median age 57 years) compared to previous studies. Fifty-one kidneys, 14 livers, 8 bilateral lungs and 2 pancreas were transplanted. One year death-censored kidney survival was 93.8%. One year liver survival was 92.8% with no case of ischemic cholangiopathy. One year lungs survival was 87.5%. Both combined pancreas/kidneys recipients are functioning. Conclusions: The use of abdominal nRP with premortem interventions represents a significant advance to increase the number and quality of grafts recovered in cDCD. Abdominal nRP combined with RR of the lungs is safe for both abdominal and thoracic grafts. The poor outcome in cDCD liver transplantation can be reversed using abdominal nRP. Donor age for cDCD liver donors may be increased safely. Further studies are needed to confirm our findings and to explore the impact of abdominal nRP on donor age, upper limit for functional warm ischemic time, ischemic injury modulation or duration of regional perfusion. We thank to Hospital Universitario Cruces (Bilbao), Complexo Hospitalario Universitario A Coruña, Hospital Clinic (Barcelona), Hospital del Mar (Barcelona), Hospital Universitario de Alicante, Hospital Clinico (Valladolid) and Hospital Miguel Servet (Zaragoza) for their help in obtaining data from their kidney and liver recipients.